Anchor Establishment Factors: Phenomenological Study of the Rejection Towards Banking Payroll - Aad Satria Permadi; Faturochman Faturochman (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2015)
Muhammadiyah owns 16,346 kindergartens across Indonesia. In Yogyakarta, out of 212 kindergartens listed in the government, 70 belong to Muhammadiyah (30%). Cumulatively, distribution of money in Yogyakarta's Muhammadiyah kindergarten is significant; however none of the kindergartens use the banking payroll system, making it vulnerable to financial exploitation and corruption. There is a rejection towards this banking payroll system. The current study aims to understand the factors influencing such rejection. Qualitative approach used in the study was phenomenology. Results from in-depth interviews and focus group discussions (FGD) on five teachers showed that anchors were established through the dynamics of two factors: leadership experience and belongingness. Variations between the factors create a new layer of anchor. More participants are needed to better understand the forming of anchors, as well as statistical analysis to validate the new anchor.